Age–Mechanic–Function (AMF) Framework: A Developmental Framework for Analyzing Cognitive and Social Learning Opportunities in Analog Board Games for Children Aged 3–8 - Prisyafandiafif Charifa; Syaiful Lokan; Ima Apriliani (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to construct and preliminarily appraise the Age–Mechanic–Function (AMF) Framework as a systematic, evidence-informed framework for analyzing cognitive and social learning opportunities in analog board games designed for children aged 3–8 years. The study combined an integrative review, structured content analysis of a purposive sample of 20 commercially available games, and a preliminary expert appraisal involving three experts in game facilitation, game design, and early childhood education. The 20 games were purposively selected based on variation in game mechanics, reported availability, and market visibility, and satisfied the predefined inclusion and exclusion criteria by spanning all three proposed developmental age ranges and representing the full spectrum of proposed mechanic families. The framework distinguishes among proposed design range, mechanic demands, potential practice opportunities, demonstrated outcome evidence, evidence directness, and facilitation conditions. For the experts’ ratings of the original combined game-level mappings, ordinal Krippendorff’s alpha was .860, while pairwise unweighted kappa values ranged from .798 to .805. These estimates indicate substantial agreement in category assignments within the small expert panel but do not establish developmental validity, causal effects, or validated age cutoffs. Accordingly, the AMF Framework is proposed as a transparent decision aid for generating and comparing design hypotheses rather than as a diagnostic tool or an alternative safety-rating system. Broader expert consensus and prospective studies involving children are needed before claims regarding learning effectiveness can be made. The AMF Framework may support game developers in designing learning mechanics that are informed by available evidence and provide early childhood educators with a structured basis for evaluating and integrating educational board games into classroom practice.